Potency of Guava Leaf Extract (Psidium guajava L.) as a Cosmetic Formulation: A Narrative Literature Review - Desri Ayu Lestari; Nopi Sulastri; Oktavia Rajebi; Nia Yuniarsih (HM Publisher, 2022)
Guava (P. guajava L., Myrtaceae) is one of the fruit plants that is widespread in the tropics and subtropics, including South America, Africa and Asia. Traditionally this plant is often used as food, traditional medicine, dyes and others. Based on the literature review of the guava leaf plant (P. guajava L.) has many bioactive compounds that play a role in maintaining the health of the body's skin. Therefore, this plant has the potential to be the basic ingredient for the formulation of cosmetic preparations. This riview literature aims to find out thetension of guava leaves (P. guajava L. ) as a basic ingredient in the manufacture of natural ingredients cosmetics. The results of this literature review show that guava leaves (P. guajava L.) has many benefits for cosmetics, namely guava leaves (P. guajava L.) can be used as an anti-acne cleanser, body scrub, lotion, deodorant, toner, and face cream.